Effect of three oral pathogens on the TMA-TMAO metabolic pathway - Wang, Xixuan; Chen, Liyuan; Teng, Ye; Xie, Weige; Huang, Lingyan; Wu, Juan; Wang, Hongwei; Xie, Sijing (Frontiers in Cellular and Infection Microbiology, 2024)
R1-2) Background: Trimethylamine-N-oxide (TMAO) is produced by hepatic flavin-containing monooxygenase 3 (FMO3) from trimethylamine (TMA). High TMAO levels is a biomarker of cardiovascular diseases and metabolic disorders, and it also effects periodontitis through interactions with the gastrointestinal microbiome.While recent findings indicate that periodontitis may alter systemic TMAO levels, the specific mechanisms between these changes and particular oral pathogens require further clarification.In this study, we established a C57BL/6J male mouse model by orally administering Porphyromonas gingivalis (P. gingivalis, Pg), Fusobacterium nucleatum (F. nucleatum, Fn), Streptococcus mutans (S. mutans, Sm) and PBS was used as a control. We conducted LC-MS/MS analysis to quantify the concentrations of TMAO and its precursors in the plasma and cecal contents of mice. The diversity and composition of the gut microbiome were analysed using 16S rRNA sequencing. TMAO-related lipid metabolism and enzymes in the intestines and liver were assessed by qPCR and ELISA methods. We further explored the effect of Pg on FMO3 expression and lipid molecules in HepG2 cells by stimulating the cells with Pg-LPS in vitro.The three oral pathogenic bacteria were orally administered to the mice for 5 weeks. The Pg group showed a marked increase in plasma TMAO, betaine, and creatinine levels, whereas no significant differences were observed in the gut TMAO level among the four groups. Further analysis showed similar diversity and composition in the gut microbiomes of both the Pg and Fn groups, which were different from the Sm and control groups. The profiles of TMA-TMAO pathway-related genera and gut enzymes were not significantly different among all groups. The Pg group showed 2 significantly higher liver FMO3 levels and elevated lipid factors (IL-6, TG, TC, and NEFA) in contrast to the other groups. In vitro experiments confirmed that stimulation of HepG2 cells with Pg-LPS upregulated the expression of FMO3 and increased the lipid factors TC, TG, and IL-6.This study conclusively demonstrates that Pg, compared to Fn and Sm, plays a critical role in elevating plasma TMAO levels and significantly influences the TMA-TMAO pathway, primarily by modulating the expression of hepatic FMO3 and directly impacting hepatic lipid metabolism.